Mental health support apps and 'proper distance': relational ethics in mHealth. (May 2019) - Shaw, Frances; McCosker, Anthony
MHealth programmes and apps have been developed by organisations like Beyond Blue and the Black Dog Institute, as tools to help people manage their mental health. The pace of development raises questions about ensuring sustained engagement and an ethical approach. Derived from ethnographic research at each organisation, this article explores reflections by research and development workers on the relational aspects of technology development, how this is negotiated and considered within mental health organisations, and the mediated relationship between users and organisations as a result. We use Silverstone's concept of 'proper distance' alongside Levinas' conceptualisation of responsibility to explore the relational ethics of apps. We argue for the importance of relational ethics in mobile mental health, in the way that medical ethics considers the doctor–patient relationship.